2016
DOI: 10.1186/s12978-016-0257-2
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women’s perceptions of exposure to brominated flame retardants

Abstract: BackgroundRecent media reports on human studies associating brominated flame retardants (BFRs) in household products in pregnancy with urogenital anomalies in boys and endocrine disruption in both sexes. We sought to explore the perceptions of pregnant women of brominated flame retardant (BFR) exposure, in light of recent media reports on the adverse health effects of BFR exposure prenatally.MethodsPregnant women were recruited for interviews through posters and pamphlets in prenatal clinics, prenatal fairs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This finding is surprising, as pregnancy is a period of high vulnerability when expectant parents should be informed about environmental risks to the development of their future child. This lack of awareness among pregnant women has already been highlighted in previous studies: it has been spontaneously expressed by pregnant women in qualitative studies [ 46 ] and found in quantitative studies. Teysseire et al [ 30 ] showed that 82% of women considered that they were not sufficiently informed about environmental risks and only 45% of the subjects were informed about environmental risks by a physician.…”
Section: Discussionmentioning
confidence: 88%
“…This finding is surprising, as pregnancy is a period of high vulnerability when expectant parents should be informed about environmental risks to the development of their future child. This lack of awareness among pregnant women has already been highlighted in previous studies: it has been spontaneously expressed by pregnant women in qualitative studies [ 46 ] and found in quantitative studies. Teysseire et al [ 30 ] showed that 82% of women considered that they were not sufficiently informed about environmental risks and only 45% of the subjects were informed about environmental risks by a physician.…”
Section: Discussionmentioning
confidence: 88%
“…That is concordant with a French local survey on environmental health where 47.4% of subjects interrogated in the general population had not heard about EDC and 68.8% felt that they did not know about their effect on health [ 35 ]. It is necessary to inform women about EDC, especially since they want to know its health effects, and consequently make informed choices [ 36 , 37 ]. The most widely named molecules were Pesticides, Bisphenol A and Parabens, which is concordant with a French study [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the survey carried out by Rouillon et al, 54.3% of 300 French women who were interviewed during pregnancy or in the first days after the birth of their child had never heard about EDCs [74]. Little knowledge of the possible risks derived from contamination with EDCs was also reported in Canada [75]. Moreover, only a minority of medical doctors who follow pregnant mothers dedicate enough time to instructing the mothers on the prevention of the environmental risks and, in turn, they often feel culturally inadequate for this task [76].…”
Section: Preventionmentioning
confidence: 99%